Description of Family Support for People Living with HIV-AIDS at KDS Dahlia - Jentri Missa; Imelda F. E. Manurung; Amelya Betsalonia Sir (Lontar : Journal of Community Health, 2020)
Human Immunodeficiency Virus & Acquired Immune Deficiency Syndrome (HIV-AIDS) is one of the global health problems whose number of sufferers continues to increase every year. A person diagnosed with HIV-AIDS will experience various reactions, such as feelings of fear, regret, trying to deny it, depression, confusion and not knowing what to do. Therefore, getting support from their families helps them to develop themselves. The purpose of this study was to determine the description of family support for people with HIV-AIDS in KDS Dahlia. This research is descriptive quantitative. The sample of this study was 77 families of people with HIV-AIDS assisted by KDS Dahlia with a total sampling technique. Data collection used a questionnaire which was analyzed univariably. The results showed that family support in the form of emotional support for people with HIV-AIDS in the poor category was 16.9% and in the good category was 83.1%, family support in the form of instrument support for people with HIV-AIDS in the less category was 31, 2% and in the good category at 68.8%, family support in the form of information support for people with HIV-AIDS in the less category of 33.8% and the good category at 66.2%, family support in the form of reward support for people with HIV-AIDS in the poor category was 16.9% and in the good category was 83.1%. Conclusion: The overall description of family support for people with HIV-AIDS can be categorized as good.